2006
DOI: 10.1007/s10532-006-9094-2
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption and biodegradation of pentachlorophenol (PCP) in an upflow anaerobic sludge blanket (UASB) reactor

Abstract: In order to understand the fate of PCP in upflow anaerobic sludge blanket reactor (UASB) more completely, the sorption and biodegradation of pentachlorophenol (PCP) by anaerobic sludge granules were investigated. The anaerobic granular sludge degrading PCP was formed in UASB reactor, which was seeded with anaerobic sludge acclimated by chlorophenols. At the hydraulic retention time (HRT) of 20-22 h, and PCP loading rate of 200-220 mg l(-1) d(-1), UASB reactor exhibited good performance in treating wastewater w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In one previous study, there was evidence that abiotic remediation accounted for more than about 30% of the total RDX loss in cold marine sediment 26. In another study, the results showed that sorption capacity of pentachlorophenol on anaerobic granular sludge was limited 27. The sorption abilities may be different for various sludges.…”
Section: Resultsmentioning
confidence: 93%
“…In one previous study, there was evidence that abiotic remediation accounted for more than about 30% of the total RDX loss in cold marine sediment 26. In another study, the results showed that sorption capacity of pentachlorophenol on anaerobic granular sludge was limited 27. The sorption abilities may be different for various sludges.…”
Section: Resultsmentioning
confidence: 93%
“…The simulation results show that, compared with the single loop flow formation and Newtonian fluid, non Newtonian fluid in the reactor was formed by two circular flow, the turbulence characteristics in the anaerobic reactor difference distribution, local turbulence is more intense, which is not conducive to the mixed fluid in the anaerobic reactor, in the design of high concentration anaerobic reaction device should consider the effects of none Newtonian fluid properties. Ye Qunfeng [6] of UASB reactor were preliminary numerical simulation of single-phase flow, factors for treatment effects of reaction, the flow characteristics through the simulation of the whole flow field in the reactor, and provide the basis for the optimization design. In the course of the study, a linear algebraic equations based on the finite element method, the Seidel iterative method for the UASB reactor for hydraulic calculation, and based on the flow field in a reactor for simulation and analysis of flow.…”
Section: Summary Of the Simulation Of Flow Field In The Anaerobic Rea...mentioning
confidence: 99%
“…A rotating brush biofilm reactor was studied for the optimum operating conditions to remove 2,4,6-Trichlorophenol (TCP) from wastewater(Eker and Kargi 2007). An investigation of biosorption and biodegradation of pentachlorophenol (PCP) in upflow anaerobic sludge blanket reactor (UASB) reported 99.5% reduction of PCP at HRT of 20 to 22 h and identified biodegradation as the main mechanism for removal other than volatization or sorption(Ye and Li 2007). Another study was done on biodegradation of catechol through co-metabolism with glucose in an UASB reactor(Subramanyam and Mishra 2007).A novel scheme called immobilized-cell-augmented activated sludge (ICAAS) was developed for bioaugmentation of completely mixed activated sludge treating a PCP pulse loading (Jittawattanarat et al 2007).…”
mentioning
confidence: 99%